Disseminated histoplasmosis from western Mexico—rethinking our geographic distribution of endemic fungal species: a case report and review of literature - Richard Sleightholm; Daniel Z. Hodson; Isabella So; Harshika Avula; Jagmohan Batra (Journal of Medical Case Reports)
Abstract Background Histoplasma is a fungal pathogen found in many parts of the world. In North America, its distribution is traditionally thought to be endemic to the Ohio and Mississippi River valleys. Development of histoplasmosis after Histoplasma exposure is related to degree of inoculum exposure and susceptibility, for example, immunocompromised status. Most exposed, healthy individuals are asymptomatic and few develop pulmonary symptoms. A limited number of infectious etiologies (that is, Histoplasma, Coccidioides, and Mycobacterium tuberculosis) can cause miliary pattern on chest imaging, and thus, histoplasmosis should be considered whenever a patient presents with pulmonary symptoms and these unique radiographic findings. Case presentation A previously healthy 13-year-old Hispanic male presented as a transfer from an outside hospital with fever and hypoxia in the setting of a progressive, subacute gastrointestinal illness. Given hypoxia, the concern for sepsis, and unclear etiology of his illness, broad-spectrum antimicrobial therapy and noninvasive ventilation were started. Initial evaluation demonstrated miliary pulmonary infiltrates, and travel history raised suspicion for coccidioidomycosis or tuberculosis. After a complete evaluation, lab studies confirmed a diagnosis of histoplasmosis, and the patient made a full recovery after the initiation and completion of antifungal therapy. Conclusion Herein, we present a patient who acquired histoplasmosis from an area of Mexico not currently acknowledged as endemic and review recently published data emphasizing new areas of Histoplasma endemicity in North America, particularly the southwest USA and most states of Mexico. Though limited surveillance data exist, mounting case reports/series and local epidemiologic studies illustrate the expanding worldwide endemicity of Histoplasma and underscore histoplasmosis as a growing global health concern.